2019
DOI: 10.1155/2019/2715968
|View full text |Cite|
|
Sign up to set email alerts
|

Frizzled-10 Extracellular Vesicles Plasma Concentration Is Associated with Tumoral Progression in Patients with Colorectal and Gastric Cancer

Abstract: Extracellular vesicles (EVs) are involved in intercellular communication during the carcinogenesis. Our attention has been focused on small EVs (sEVs) protein content in colorectal and gastric cancer (CRC and GC). Frizzled (FZD) proteins, a family of receptors comprised in the Wnt signaling pathway, play an important role in the carcinogenesis of CRC and GC. Here, the expression of a specific FZD protein, namely, FZD-10, was investigated in the sEVs extracted from plasma of patients affected by CRC and GC as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…The in vitro findings suggest that FZD10-and FZD10-mRNA-delivering exosomes may be potential messengers of cellular transformation that are able to play an active function in the long-distance metastatization process [42]. The involvement of FZD10 vehiculated in small extracellular vesicles (sEVs) in the control of cancer progression and cancer cell modification has also been suggested by another previous clinical study [43]. In particular, the expression of FZD10 in EVs extracted from the plasma of patients affected by CRC and GC has been investigated, before and after treatment (surgery, chemotherapy, and metastasis removal), by using the protein expression in the EVs from the plasma of healthy subjects as a reference.…”
Section: Role Of Exosomes In Tumorigenesis Of Gastrointestinal Cancerssupporting
confidence: 52%
“…The in vitro findings suggest that FZD10-and FZD10-mRNA-delivering exosomes may be potential messengers of cellular transformation that are able to play an active function in the long-distance metastatization process [42]. The involvement of FZD10 vehiculated in small extracellular vesicles (sEVs) in the control of cancer progression and cancer cell modification has also been suggested by another previous clinical study [43]. In particular, the expression of FZD10 in EVs extracted from the plasma of patients affected by CRC and GC has been investigated, before and after treatment (surgery, chemotherapy, and metastasis removal), by using the protein expression in the EVs from the plasma of healthy subjects as a reference.…”
Section: Role Of Exosomes In Tumorigenesis Of Gastrointestinal Cancerssupporting
confidence: 52%
“…The restoration of the cell viability, as well as of the FZD10 and FZD10-mRNA level, was promoted by incubation of silenced cells with the exosomes isolated by culture medium of the same untreated cells [ 21 ]. Remarkably, our clinical study established an active role for FZD10, delivered in small extracellular vesicles, as a potential biomarker for the early diagnosis of CRC and gastric cancer and for monitoring the treatment response [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an in vitro study suggested that FZD10 and FZD10-mRNA delivering exosomes may be potential messengers of disease reactivation even in quiescent cells. Moreover, FZD10 delivering exosomes are also thought to function as messengers of cellular transformation, with a concomitant possible active role in metastasis were supposed [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then cells were blocked with an aqueous solution of normal serum (5%) in PBS for 1 h and incubated at 4 °C over-night with the two primary antibodies mix. The protocol applied has been previously described [ 19 ], with the following antibodies: mouse monoclonal anti human Vimentin (diluted 1:250 in Blocking) and rabbit polyclonal anti human phospho-Paxillin (Tyr118) (diluted 1:200 in Blocking). Then, cells were washed twice with PBS and incubated with a specific green-fluorescent (goat anti-mouse IgG (H + L) secondary antibody Alexa Fluor 488 conjugate) and red-fluorescent (goat anti-rabbit IgG (H + L) superclonal secondary antibody, Alexa Fluor 555) secondary antibodies for 1 h, at room temperature, in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, numerous studies proved that FZDs play a crucial role in different cancer functions, thus promoting proliferation, migration, invasion, angiogenesis, and also chemoresistance. Furthermore, modulation of expression levels for specific FZD depending on up- or downregulation of the corresponding messenger RNA (mRNA) was observed in different cancers tissues [ 15 , 16 , 17 , 18 , 19 , 20 ]. Among the FZD proteins, FZD10 was suggested to be one of the most promising receptors for the development of targeted therapy of CRC.…”
Section: Introductionmentioning
confidence: 99%